2019
DOI: 10.1590/1807-3107bor-2019.vol33.0020
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of HLA-G and FoxP3+ T regulatory cells in oral cavity and lower lip squamous cell carcinomas

Abstract: Human Leukocyte Antigen G (HLA-G) is a molecule involved in the tumor immunosuppression and also in the generation of regulatory T (Treg) cells, thus leading to evasion to the immune system host, and consequently, contributing to tumor progression in several cancers. The aim of this study was to evaluate the immunoexpression of HLA-G by tumor cells and FoxP3+ Treg cells in 25 oral tongue squamous cell carcinomas (SCCs) and 25 lower lip SCCs and analyze their relationship with clinical parameters. HLA-G express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A larger number of these cell types in the microenvironment of OSCC have been associated with more advanced stages and worse prognosis 16,17,27,28 or with initial stages and higher survival rates. 18,29 The reasons for these discrepancies remain unclear, but the findings of the present study suggest that patient age could be an important confounding factor. In line with this suggestion, previous studies that have correlated the number of Treg cells in the microenvironment of OSCC with the progression and prognosis of these malignancies, have used samples from young and older individuals, aged 26 to 92 years.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A larger number of these cell types in the microenvironment of OSCC have been associated with more advanced stages and worse prognosis 16,17,27,28 or with initial stages and higher survival rates. 18,29 The reasons for these discrepancies remain unclear, but the findings of the present study suggest that patient age could be an important confounding factor. In line with this suggestion, previous studies that have correlated the number of Treg cells in the microenvironment of OSCC with the progression and prognosis of these malignancies, have used samples from young and older individuals, aged 26 to 92 years.…”
Section: Discussionmentioning
confidence: 63%
“…In line with this suggestion, previous studies that have correlated the number of Treg cells in the microenvironment of OSCC with the progression and prognosis of these malignancies, have used samples from young and older individuals, aged 26 to 92 years. 16,17,28,29 Information on possible sex-related differences in the number of Treg cells in the microenvironment of OSCC is scarce. 27 Kouketsu et al, 27 in a study on OSCC diagnosed in individuals aged 27 to 93 years, did not observe significant differences in the number of FoxP3+ lymphocytes in the microenvironment of lesions associated with patient sex.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G is a non-classical human leukocyte antigen class I molecule which inhibits the activities of T lymphocytes, NK cells, and antigen-presenting cells. [21][22][23][24] In this study, we found that when HLA-G expression was down-regulated in A549 cells by transfecting miR-152 mimics or siRNA, more A549 cells could be recognized and lysed by NK cells. A similar association between HLA-G expression and the NK cell-killing effect was reported in other cancers such as melanoma, 25 choriocarcinoma, 26 leukemia, 27 ovarian cancer, 28,29 and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 69%
“…Likewise, in lung-cancer patients, CD103+ lymphocytes have been found to be a positive predicted marker for checkpoint inhibitor therapy responses [ 165 ] and found to be associated with a prognostic benefit in cervical-cancer patients [ 166 ]. Additionally, the presence of regulatory T cells (Tregs) has been shown to be a negative prognostic biomarker in gynecologic cancer, oral squamous cell carcinoma, and prostate cancer [ 167 , 168 , 169 ]. In mice bearing melanoma treated with anti-PD-1 immunotherapy, another group has shown that the secretion of INF-y from peripheral lymphocytes can be an accurate biomarker predictive of treatment response [ 170 ].…”
Section: Biomarkers In Immunotherapymentioning
confidence: 99%